Utilização de bentonita e fibra de sisal como adsorventes na remoção do antibiótico amoxicilina - Araújo, Pricila de Souza (2022)
The risks and impacts of antibiotics on the environment is a problem that has drawn the attention of researchers, since the continuous release of effluents contaminated with these substances, associated with the lack of efficient treatment technologies, is still a challenge. Considering that amoxicillin is one of the most prescribed antibiotics in Brazil and in the world, the main objective of this work was to evaluate bentonite and sisal fiber as adsorbents in the adsorption of amoxicillin in an aqueous medium. The adsorbents were characterized by zero charge point techniques, X-ray diffraction, X-ray fluorescence, Boehm titration, Fourier transform infrared spectroscopy, thermogravimetry, scanning electron microscopy and physical N2 adsorption. The adsorption tests occurred with variation of concentration (10 ppm to 100 ppm) and temperature (23 ºC, 33 ºC, 43 ºC). The influence of the adsorbent mass and pH of the medium were also investigated. Through the characterization analysis it was verified that the bentonite is of the calcium type, mesoporous (9.86 m2.g-1), with a heterogeneous structure formed by aggregates of smaller particles. Sisal is also a mesoporous material (2,19 m2.g-1), fibrous with a rough surface and a fine and compacted cell arrangement, the fiber surface functional groups present the following order: carboxylic (–COOH) > lactones (–COOR) > phenolics (–OH). Kinetic data for bentonite followed the pseudo-first order model, reaching 92.3 % removal in 360 min of assay with adsorption capacity of 0.92 mg.g-1. For sisal, the kinetics followed the pseudo-second order model, reaching 17.2 % removal in 300 min with adsorption capacity of 1.72 mg.g-1. The isotherm models for both adsorbents at the temperature of 23 ºC were adjusted to the Langmuir model, for 33 ºC they followed the Sips model and for the temperature of 43 ºC, the isothermal data for bentonite followed the Sips model and for sisal the model from Langmuir. The thermodynamic data indicated that the nature of the adsorption process was spontaneous and exothermic, except for adsorption with sisal at a temperature of 43 ºC. Bentonite is an effective adsorbent for removing amoxicillin in adsorption treatment systems. When compared to bentonite, sisal did not present equivalent results, but because it is a natural, low-cost and easily accessible material, it can still be thought of as an alternative adsorbent.